Educational Language Polices in Nigeria and Zimbabwe: The Role of Educational Inclusion - Tom-Lawyer, Oris; Thomas, Michael (European Scientific Journal, ESJ, 2026)
Educational language policies in African countries are controversial as their colonial legacies continue to undervalue indigenous African languages (Sibomana, 2015). These policies, such as the Education Act (1987) in Zimbabwe, influences the future of African children as they do not always support linguistic inclusion, which in turn may impact the social, economic and national development of a country. While this context is applicable to most African countries, few comparative studies to date have been undertaken to explore this subject in more depth. To address this gap, this study is the first to examine the need for educational inclusion in the language polices of Nigeria and Zimbabwe, two of the continent’s largest economies, as both have a two-language system (Anukaenyi, 2019) and English is still hegemonic (Chivhanga and Chimhenga, 2013). The study is based on the premise that detrimental medium of instruction policies at the national level can damage learning, access and inclusion (Cele, 2021). The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta Analyses) guided the critical review of 80 publications in the study which spanned more than two decades (2000-2024). Findings suggest that the policies have encouraged the marginalisation of indigenous languages and harmed students, as their learning continues to take place in an unfamiliar language. Furthermore, the language policies in both countries have also promoted inequality as they have not been implemented in private schools. The study recommends the need for more comparative research on the importance of inclusive teaching and learning of English alongside learners’ indigenous languages to improve effective and equitable policy implementation